2018
DOI: 10.1111/anae.14444
|View full text |Cite
|
Sign up to set email alerts
|

Changes in health‐related quality of life after discharge from an intensive care unit: a systematic review

Abstract: Summary Quality of life after critical illness is becoming increasingly important as survival improves. Various measures have been used to study the quality of life of patients discharged from intensive care. We systematically reviewed validated measures of quality of life and their results. We searched PubMed, CENTRAL, CINAHL, Web of Science and Open Grey for studies of quality of life, measured after discharge from intensive care. We categorised studied populations as: general; restricted to level‐3 care or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 74 publications
(223 reference statements)
8
101
1
2
Order By: Relevance
“…Also, HRQoL at admission was associated with both LOS and readmission. Several previous studies have reported that HRQoL returns to population norms one year or longer after discharge from intensive care units [20]. In our study, we found that HRQoL showed partial improvements even as early as at discharge.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Also, HRQoL at admission was associated with both LOS and readmission. Several previous studies have reported that HRQoL returns to population norms one year or longer after discharge from intensive care units [20]. In our study, we found that HRQoL showed partial improvements even as early as at discharge.…”
Section: Discussionsupporting
confidence: 62%
“…For elderly patients hospitalized for acute illness, HRQoL is known to be an important determinant of hospital outcomes (e.g., LOS) [9,[20][21][22][23], although in dispute, other studies reported no relationship [24]. Higher baseline HRQoL is considered to have better functional reserves or ability to recover and could thus predict shorter hospital stays [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, Orwelius and colleagues 30 showed that the effect of ICU admission on the proportion of patients reporting pain (44.3% of the post-ICU population vs 25.7% of those that were not admitted to the ICU) was mitigated once the number of pre-existing co-morbidities was accounted for in the reference population. A systematic review of HRQoL after ICU discharge, including 48 studies, 18 identified a significant decrement in pain domains compared with population norms when using the EQ-5D at 12 months (20 studies). However, when the SF-36 was used (30 studies), this decrement was not significant, and it is unclear whether the different results can be accounted for by the choice of outcome measure or other study-specific characteristics.…”
Section: Prevalencementioning
confidence: 99%
“…Interventions to help recover from critical illness are likely to affect areas such as physical function and social ability, especially during the rst year after hospital discharge. [31].…”
Section: Life After Critical Illnessmentioning
confidence: 99%